Uji Aktivitas Dan Formulasi Sediaan Sampo Ekstrak Daun Nilam (Pogostemon Cablin Benth.) Terhadap Malassezia Furfur - Julia Megawati Djamal; Asti Artika Arbie; Alya Meisyara Pusila; Afrid Trifena Puteri Kanalung; Sri Nindi Saribulan; Farhan Didipu (Jurnal Ners, 2026)
Dandruff is a condition characterized by abnormal flaking of the scalp. The cause of dandruff is still unknown, but Malassezia furfur can generally cause dandruff. Patchouli leaves (Pogostemon cablin Benth.) contain chemical compounds including essential oils, flavonoids, saponins, tannins, phenols, terpenoids, and steroids, which have antimicrobial, antioxidant, and anti-dandruff properties. The purpose of this study was to determine the formulation of shampoo preparations and the activity of patchouli leaves (Pogostemon cablin Benth.) against Malassezia furfur. The stages of this study were sample preparation, extract preparation, stock solution preparation, test medium preparation, test fungus preparation, fungus suspension, patchouli leaf extract activity test, shampoo preparation, and physical stability evaluation. The best formulation for an anti-dandruff shampoo preparation was formula I with a 1% HPMC concentration, and the strongest inhibitory activity against Malassezia furfur was observed at a 30% concentration with an inhibition zone diameter of 33.25 mm.